2008
DOI: 10.1007/s00449-008-0233-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aeration and agitation on the protease production by Staphylococcus aureus mutant RC128 in a stirred tank bioreactor

Abstract: The modified rotating simplex method has been successfully used to determine the best combination of agitation rate and aeration rate for maximum production of extracellular proteases by Staphylococcus aureus mutant RC128, in a stirred tank bioreactor operated in a discontinuous way. This mutant has shown altered exoprotein production, specially enhanced protease production. Maximum production of proteases (15.28 UP/ml), measured using azocasein as a substrate, was obtained at exponential growth phase when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
0
18
0
2
Order By: Relevance
“…Skowronek and Fiedurek used simplex method to optimize five different medium components for production inulinase by Aspergillus niger [20]. The Simplex method has been adopted to find optimal aeration and agitation rates for protease production by Staphylococcus aureus mutant in a stirred tank bioreactor [21]. A rotating simplex method was employed to determine the best suitable fermentation conditions for batch production of chitinase [22].…”
Section: Introductionmentioning
confidence: 99%
“…Skowronek and Fiedurek used simplex method to optimize five different medium components for production inulinase by Aspergillus niger [20]. The Simplex method has been adopted to find optimal aeration and agitation rates for protease production by Staphylococcus aureus mutant in a stirred tank bioreactor [21]. A rotating simplex method was employed to determine the best suitable fermentation conditions for batch production of chitinase [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the fermentation process using an aerobic culture, the oxygen affects the production of enzymes due to the changes in the metabolic pathway and metabolic fluxes (Calik et al, 1998). Ducros et al (2009) suggested that the respiration rate of the aerobic culture is dependent on the dissolved oxygen. This is due to physiological alteration in cell metabolism (Hwang et al, 1991).…”
Section: Protease Production In Original and Optimised Mediummentioning
confidence: 99%
“…109,110 This method, however, does not give consistent results when compared with the steady-state method of measurement of oxygen uptake rate. The most probable cause of the discrepancy between measurements by the dynamic and steady-state methods is due to the effect of very small gas bubbles in viscous broths.…”
Section: Dynamic Methodsmentioning
confidence: 74%
“…Ducros et al 110 determined the k L a values from the transient data of dissolved oxygen obtained during degassing and aeration periods. The probe response was corrected by the first-order lag model.…”
Section: Dynamic Methodsmentioning
confidence: 99%